Contraindications and factors that rule out patients willing to undergo laser vision correction - Jan Łoginoff; Przemysław Morawski; Filip Pactwa; Ewa Szymańska; Sandra Ostaszewska; Kinga Świąder; Kinga Augustynowicz; Jakub Chrzanowski; Bartłomiej Wójcik; Zuzanna Popińska (Kazimierz Wielki University, 2023)
Laser vision correction is a modern method of eliminating, not just correcting, vision defects. The laser results in the restoration of the patient's eyes, so that he or she gains visual acuity anew. This method is both effective and safe, however, it is not feasible for every person. There are certain restrictions regarding: age, health, type of defect, history of disease, corneal scarring, pregnancy (both during and planned), or breastfeeding. Other rather non-obvious limitations, often overlooked by patients at the qualifying examination, are a metal filing that once found its way into the eye, after which it was removed rather late by a specialist, or current dry eye syndrome. The procedure of laser vision correction, can be carried out only after obtaining both the consent of the doctor conducting the qualifying examination and the interested party himself.